Produção de cervejas de alta fermentação utilizando linhagens indígenas de Saccharomyces cerevisiae - Fábio Ferreira Florêncio (2021)
The production of beer in Brazil is still mostly dependent on the importation of yeast strains for its preparation, which causes high costs. There are few companies in Brazil that produce national yeasts and make them available to breweries, resulting in beers with little national identity. This study aimed to test two previously selected and isolated indigenous Saccharomyces cerevisiae yeast strains, of spontaneous fermentation must of ‘cachaça’, identified as potential candidates for craft beer production. This research tested two yeast strains concomitant with a commercial strain, on a 20-liter scale, manufactured according to the home brewer mold. After beer production, sensory analyses were performed, and a questionnaire for purchase intention and preference test was applied. The most preferred beer was taken to an industrial production at LOBA brewery in Santana dos Montes (MG), where it was used in the development of a recipe, called Belgian Pale Ale, based on the Belgian School for the production of 1,500 liters. After industrial production, the beer underwent a new sensory analysis and purchase intention. The results showed that the selected strain Y228 had positive analyses during the sensory tests. The beers produced were also characterized in relation to the production of esters, phenols, higher alcohol and other metabolites. The acceptance during the sensory analysis of the produced beers was similar to the beer used as control and fermented with a commercial yeast strain. This research showed that the studied strains can be part of the catalog of yeasts used for beer production in Brazil, contributing to a greater supply of typically Brazilian brewing strains.